Adaptation and feasibility of WHO PM+ for adolescents living with HIV in KwaZulu-Natal Province, South Africa: an implementation feasibility study protocol - Maryam Shahmanesh; Kathy Baisley; Nothando Ngwenya; Marit Sijbrandij; Alan Stein; Janet Seeley; Soraya Seedat; Grace Nduku Wambua (BMJ Open)
Introduction Adolescents living with HIV (ALHIV) are an extremely vulnerable population, with the burden of mental health problems carefully documented together with the constraints for receiving timely and adequate management of the problems, especially in rural settings. Problem Management Plus (PM+) is a scalable psychological intervention for individuals impaired by distress in communities exposed to adversity. Initially developed for adult populations, few studies have assessed its potential to address adolescent distress. This study aims to co-adapt PM+ with an adherence component (PM+Adherence) for ALHIV and to evaluate its acceptability and feasibility in rural Kwa-Zulu Natal Province, South Africa.Methods and analysis We will use a mixed-methods approach over three phases. The first phase will include a realist synthesis and collection of formative data from up to 60 ALHIV, caregivers and healthcare providers to inform the adaptation of WHO PM+, including the components of an adherence module. During the second phase, we will undertake the cultural adaptation of the PM+Adherence intervention. The third phase will involve a hybrid type 3 implementation strategy among ALHIV aged 16–19 years (n=50) to implement and evaluate the feasibility of the culturally co-adapted PM+Adherence. The feasibility indicators to be evaluated include reach, adoption, attrition, implementation and acceptability of the adapted intervention, which will be assessed qualitatively and quantitatively. In addition, we will assess preliminary effectiveness using an intention-to-treat approach on HIV-related indicators and mental health outcomes at baseline, end intervention, 2-month follow-up during the 6-month implementation.Discussion We expect that the PM+Adherence will be acceptable and can feasibly be delivered by lay counsellors in resource-limited rural KwaZulu-Natal.Ethics and dissemination Ethical clearance has been obtained from the University of KwaZulu-Natal Biomedical Research Ethics Committee, (BREC/00005743/2023). Dissemination plans include presentations at scientific conferences, peer-reviewed publications and community level.